IS AN UP-TO-DATE EDUCATIONAL PUBLICATION, DEDICATED TO THE PECULIARITIES OF INVESTIGATION OF CERTAIN TYPES OF OF CRIMES - Чорноус, Ю.М (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2016)
In his review, Doctor of Law Yu. M. Chornous commends the textbook Investigation of Certain Types of Crimes (edited by M. A. Pohoretskyi and D. B. Serhieieva, 2015) as a timely and relevant educational resource following the adoption of the 2012 Criminal Procedure Code of Ukraine. The author highlights the necessity of updated forensic methodology to address newly criminalized offences. Comprising 14 chapters, the manual systematically presents criminalistics characteristics of specific crimes, typical investigative scenarios, and tactical methods, alongside organizational and procedural aspects of investigative and search actions. Chornous emphasizes the balanced integration of theory and practical guidance, rendering the textbook valuable both for students and cadets and for investigative practitioners within the justice system and law enforcement agencies.

У рецензії д.ю.н. Ю. М. Чорноус високо оцінюється навчальний посібник «Розслідування окремих видів злочинів» (за ред. М. А. Погорецького та Д. Б. Сергєєвої, 2015). Автор звертає увагу на його своєчасність у контексті впровадження Кримінального процесуального кодексу України 2012 р. та появи нових видів злочинів, що потребують сучасних криміналістичних методик. Видання охоплює 14 розділів, у яких висвітлено криміналістичну характеристику окремих складів злочинів, типові слідчі ситуації та тактичні прийоми, а також організаційні аспекти проведення слідчих і розшукових дій. Особлива увага приділена поєднанню теоретичних положень із практичними рекомендаціями, що робить посібник корисним як для студентів і курсантів, так і для практичних працівників органів правосуддя та силових структур.
АКТУАЛЬНЕ НАВЧАЛЬНЕ ВИДАННЯ, ПРИСВЯЧЕНЕ ОСОБЛИВОСТЯМ РОЗСЛІДУВАННЯ ОКРЕМИХ ВИДІВ ЗЛОЧИНІВ